2023
DOI: 10.1039/d3qo00861d
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic C(sp2)–OMe bond cleavage and amidation of anisoles with N-hydroxyphthalimides and phthalimides

Abstract: The cleavage of the inert C(sp2)−OMe bond via photocatalysis is an attractive alternative to the well-established Ni-catalyzed methods, and is also a challenge in organic chemistry. Herein we report a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Compared with conventional C1 synthons such as DMF, DMSO, formaldehyde, and methanol, DMEA has shown some unique activities. For instance, with the same catalyst and substrates, Zhang’s group found that amidines reacted with DMSO to afford quinazolines, while we found that 1,3,5-triazine derivatives were obtained when DMEA was utilized as a C1 synthon instead of DMSO. , Inspired by these findings and driven by our continuous interest in the synthesis of heterocycles, the construction of 2 H -chromenes involving DMEA was attempted. Herein, we wish to report an unprecedented Cu­(II)-catalyzed [3 + 1+1 + 1] annulation for the efficient synthesis of 2 H -chromenes from 2-naphthols, 1,3-diketones, and DMEA via two discrete homologations (Scheme c).…”
Section: Introductionmentioning
confidence: 94%
“…Compared with conventional C1 synthons such as DMF, DMSO, formaldehyde, and methanol, DMEA has shown some unique activities. For instance, with the same catalyst and substrates, Zhang’s group found that amidines reacted with DMSO to afford quinazolines, while we found that 1,3,5-triazine derivatives were obtained when DMEA was utilized as a C1 synthon instead of DMSO. , Inspired by these findings and driven by our continuous interest in the synthesis of heterocycles, the construction of 2 H -chromenes involving DMEA was attempted. Herein, we wish to report an unprecedented Cu­(II)-catalyzed [3 + 1+1 + 1] annulation for the efficient synthesis of 2 H -chromenes from 2-naphthols, 1,3-diketones, and DMEA via two discrete homologations (Scheme c).…”
Section: Introductionmentioning
confidence: 94%